VARIASI GENETIK Shorea macrophylla DAN Shorea stenoptera DI HUTAN ALAM DESA SUNGAI BUAYA, KABUPATEN SINTANG BERDASARKAN PENANDA MIKROSATELIT - , IRNA LESTYANINGSIH, Dr. Sapto Indrioko, S.Hut., M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Forest degradation in Indonesia led to the extinction of Shorea macrophylla and Shorea stenoptera as the major source of illipe nut (tengkawang) oil. To protect those species from being extinct, genetic conservation such in-situ conservation are necessary. The study was aimed to determine the genetic variation of S. macrophylla and S. stenoptera in natural forest population and the distribution of genetic variation in four living levels, i.e. trees, poles, saplings, and seedlings. Leaf and cambium samples of two Shorea species were collected from natural forest at Desa Sungai Buaya, Kecamatan Kayan Hilir, Sintang, Kalimantan Barat by purposive sampling. Genetic variation observed by 3 primers microsatellite marker, i.e. Shc-2, Shc-7, and Shc-9. Data were analyzed using GenAlex 6.5. The results showed that proportion of polymorphic locus is 100% of both species. The observed heterozygosity (Ho) of S. macrophylla are 0,633 (trees), 0,292 (saplings), and 0,333 (seedlings), while expected heterozygosity (He) are 0,560 (trees), 0,353 (saplings), and 0,318 (seedlings). Ho for S. stenoptera are 0,633 (trees), 0,542 (saplings), and 0,422 (seedlings), while He 0,462 (trees), 0,557 (saplings), and 0,541 (seedlings). The genetic variation of S. macrophylla derived from trees to saplings level was 46,129% and seedlings level was 52,606%, while genetic variation of S. stenoptera derived from trees to saplings level was 83,624% and seedlings level was 66,667%.